Намагниченность насыщения и теплоемкость ферромагнетика [Articol] - Клюканов, Александр; Ника, Денис (CEP USM, 2016)
Намагниченность насыщения, внутренняя энергия и дисперсия магнонов вычислены без использования модельных представлений. Показано,что температурная зависимость магнитногомомента и внутренней энергии ферромагнетика находятся в согласии с теорией, основанной на модели Гейзенберга, что является отражением резонансного характера переходов, обусловленных спинорбитальным взаимодействием.

Magnetizarea de saturaţie, energia internă şi dispersia magnonilor a u fost calculate fără folosirea reprezintărilor model. A fost demonstrat că dependenţa de temperatură a momentului magnetic şi a energiei interne a substanţei feromagnetice se află în acord cu teoria bazată pe modelul lui Heisenbergce reflectă caracterul rezonant al tranziţiilor cauzate de interacţiunea spinorbitală.

Saturation magnetization, magnon dispersion law and heat capacity of ferromagnetic are calculated from the first principles.It has been demonstrated that temperature dependence of magnetic momentum and internal energy of ferromagnetic is in a good agreement with that obtained in the framework of the Heisenberg model. The latter reflects the resonance character of the electron transitions due to the spinorbit coupling.
MAGNETIZAREA DE SATURAŢIE ŞI CAPACITATEA TERMICĂ A SUBSTANȚEI FEROMAGNETICE
SATURATION MAGNETIZATION AND HEAT CAPACITY OF FERROMAGNETIC
Keywords: намагниченность насыщения; магнон; теплоемкость; ферромагнетик; magnetizare de saturaţie; magnon; сapacitate termică; saturation magnetization; saturation magnetization; heat capacity; ferromagnetic